Multimodal Treatment With Orbital Organ Preservation in Adult Patients With Locally Advanced Small-Round-Cell Malignancy of the Nasal Cavity and Paranasal Sinus - Chen, Nanxiang; Yuan, Hu; Fan, Wenjun; Ma, Lin; Liu, Kun; Chen, Lei; Yang, Shiming; Zhang, Xinxin (Frontiers in Oncology, 2021)
Background: To investigate the efficacy of induction chemotherapy followed by concurrent chemotherapy and helical tomotherapy in adult patients with locally advanced small-round-cell malignancy of the nasal cavity and paranasal sinus in regard to orbital organ preservation and quality of life. Methods: Clinical data of 49 cases of patients with orbital involvement of locally advanced small-round-cell malignancy of the nasal cavity and paranasal sinus who received multimodal treatment for orbital organ preservation between December 2009 to January 2019 were retrospectively analysed. The treatment efficacy and side effects were assessed. The study included three different pathological types. All patients were treated with induction chemotherapy followed by concurrent chemoradiotherapy. Helical tomotherapy was applied as radiotherapy. Adverse reactions to the chemotherapy were assessed according to Common Terminology Criteria for Adverse Events, Version 3. The overall survival rate, progression free survival rate and orbital preservation rate were calculated using the Kaplan-Meier method. Results: After the multimodal treatment, The 3- and 5-year OS rates of the 49 patients were 63.8% and 54.5%, respectively, and the 3- and 5-year total PFS rates were 66.8% and 63.1%, respectively. Conclusions: Multimodal treatment could preserve the orbital organs of adult patients with small-round-cell malignancy of the nasal cavity and paranasal sinus, achieve relatively ideal organ protection and survival rates and improve the quality of life, thus providing a new treatment option for these patients.